DESAIN ANIMASI 3D PROFIL FAKULTAS TEKNIK UNIVERSITAS GAJAH PUTIH TAKENGON - Hendri Syahputra; Alpi Sahrin (Pixel :Jurnal Ilmiah Komputer Grafis, 2020)
Gajah Putih University Takengon is a private university located in Central Aceh District, Pegasing District, consisting of several faculties, one of which is the Faculty of Engineering which has one study program, namely Informatics Engineering. In promoting and informing the wider community, the Faculty of Engineering, Gajah Putih University, Takengon uses brochures and website media which the author feels that this method is still lacking in informing because not all facilities can be informed in detail, from this problem the authors conducted research on 3D animation design profile of the Faculty of Engineering, Gajah Putih University, Takengon as a promotional media. The software used in this research is Blender 2.82. In designing the system the author uses the Luther method, the Luther method has six stages, namely concept, design, collecting material, assembly, testing, and distribution.